2017
DOI: 10.1139/as-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between climate and landscape drive Holocene ecological change in a High Arctic lake on Somerset Island, Nunavut, Canada

Abstract: This study presents a diatom-based analysis of the post-glacial Holocene environmental history at Lake RS29 on Somerset Island in the Canadian High Arctic. Earliest post-glacial diatom assemblages (10 200-10 000 cal yr BP) consisted mainly of small, benthic fragilarioid taxa. Poor diatom preservation in the early Holocene (~10 000-6200 cal yr BP) is associated with warm conditions, as determined by pollen data from the same core and other paleoclimate estimates from the region. Analysis of this and other sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 97 publications
2
13
0
Order By: Relevance
“…yr BP are characterized by poor diatom preservation, few taxa and low diatom concentration. Paull et al (2017) suggest that poor diatom preservation in lake sediments records from Canadian Arctic may be associated with warmer climate conditions. Around 3700 cal.…”
Section: Discussionmentioning
confidence: 96%
“…yr BP are characterized by poor diatom preservation, few taxa and low diatom concentration. Paull et al (2017) suggest that poor diatom preservation in lake sediments records from Canadian Arctic may be associated with warmer climate conditions. Around 3700 cal.…”
Section: Discussionmentioning
confidence: 96%
“…(Table S2, Michelutti et al, 2006;Vinocur & Maidana, 2010), Pinnularia spp. (Table S2, Michelutti et al, 2006;Paull et al, 2017;Vinocur & Maidana, 2010), Eunotia spp. (Table S2; Falasco and Bona, 2011;Küttim et al, 2017) and A. minutissimum (Table 1, Keatley et al, 2006;Lotter et al, 2010) were observed during this period in lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms were apparently being deposited in the sediments, but no Chla accumulated. Large changes in diatom concentrations have been recorded in Holocene diatom studies from the Canadian Arctic, and these may be associated either with climate changes, with lake history, or with diagenesis [27]. Low diatom concentrations in sediments seem to be associated with warm temperatures at many sites, perhaps due to dissolution of the diatoms [27].…”
Section: ) the Interpretation Of Changes In The Diatom Assemblages And Production In These Short Cores Are Contradicted By Longer Sequencmentioning
confidence: 99%